Haiti : bibliography and maps ([s.n.] [S.l], 1995)
Presents a small atlas on Haiti which shows in graphic form, mostly in maps and graphs, Haiti's population - size, distribution, composition and trends, and its recent economic and agricultural situation. Includes a select bibliography which lists publications from 1990 to 1995 on topics such as economic conditions, foreign policy, politics and government and social conditions.
DC